Peran Klinik Nikah Dalam Membangun Kesiapan Menikah sebagai Upaya Pembentukan Keluarga Sakinah: - Indah Sari; Fatimah Fatimah (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This study aims to examine the role of pre-marital education in building marriage readiness and forming a sakinah family at the “KLIK” marriage clinic, Medan City Branch and find out how to minimize divorce cases, as well as the factors that motivate people to participate in the Marriage Clinic program. The method used is descriptive qualitative, by conducting research at the Medan City Branch Marriage Clinic. Data collection techniques used are interviews, observation and documentation. Data analysis was carried out by collecting data, presenting data and drawing conclusions. This study concluded that the Marriage Clinic in minimizing divorce cases is providing and adding knowledge to the community so that they are able to form a sakinah family. Have qualified and quality materials and have presenters who are experienced in their respective fields. Of course it makes it easier for the Marriage Clinic to help the community. According to the informants, the materials provided by the Marriage Clinic were able to become their basis in forming a sakinah family because the materials provided were so complete and easy to understand for the participants. Keywords: Marriage Clinic, Marriage Readiness, Sakinah Family